SHADING EFFECTS ON GROWTH AND PARTITIONING OF PLANT BIOMASS IN PASPALUM CONJUGATUM BERG - I,B IPOR (Biotropia: The Southeast Asian Journal of Tropical Biology, 2011)
Glasshouse studies were carried out to determine the effect of shading on the growth and partitioning of plant biomass in Paspalum conjugatum Berg. The invidual leaf rate expansion, final leaf are, specific leaf area, and the whole plant vegetative growth pattern, dry-matter production, leaf area as well as biomass partitioning were significantly influenced by shading. At the 75% level of shading, P. conjugatum produced the highest values of leaf weight  ratio,  specific  leaf  area  and  leaf  area  ratio.  Individual  leaf  assessment  revealed  that  shading significantly increased the final leaf area, duration of leaf expansion and specific leaf area.